Benign odontogenic ghost cell lesions revisited and new considerations on dysplastic dentin - Garcia Rosa, Ana Claudia; Teixeira, Lucas Novaes; Passador-Santos, Fabricio; Furuse, Cristiane [UNESP]; Martins Montalli, Victor Angelo; Araujo, Ney Soares de; Araujo, Vera Cavalcanti de (Springer, 2019)
Objectives This study aimed to revisit benign odontogenic ghost cell lesions (BOGCL) by hematoxylin and eosin staining and immunohistochemistry. Materials and methods Thirty cases of calcifying odontogenic cyst (COC) and 6 cases of dentinogenic ghost cell tumor (DGCT) were selected for histopathological and immunohistochemical analysis. Sections stained for cytokeratin (K) 14, K-19, amelogenin, collagen type 1 (COL-1), and dentin matrix acidic phosphoprotein 1 (DMP-1) were evaluated using qualitative analysis. Sections stained for Ki-67 and minichromosome maintenance protein-2 (MCM-2) were evaluated using semi-quantitative analysis. Results A morphologic overlap was noticed in all BOGCL. Moreover, no differences were detected in the expression of K-14 and K-19. The expression of proliferative markers Ki-67 and MCM-2 was similar between cystic and tumor lesions (p > .05). The presence of COL-1 and absence of amelogenin in the so-called dysplastic dentin, associated with its histologic pattern, suggest that this is in fact an enameloid-like tissue. Conclusions The dysplastic dentin should be considered an enameloid-like tissue in these lesions.
Keywords: Calcifying odontogenic cyst; Dentinogenic ghost cell tumor; Dentin matrix acidic phosphoprotein-1; Collagen-1; Amelogenin; Dysplastic dentin; Enameloid